PELATIHAN REKONSTRUKSI MODUL KIMIA BERBASIS BRAINSTORMING PROBLEM SOLVING MAHASISWA PPL KIMIA DALAM PERSIAPAN TUGAS AKHIR - Florida Doloksaribu; Irwandi Yogo Suaka (LPPM Uncen, 2018)
Lecture and teacher as a pillar that is expected to build quality research, education, analysis, and should have a high responsibility on the problems by this nation. The problem of un-ordinary research at the student level is very much found. Sometimes lecturers do not carefully analyze the originality of research guidance. Therefore, many researchers do not dare to publish the results of their work to the realm of accredited publications. Based on the understanding and several lecture models and modules that have been studied, designed, or developed, it is necessary to provide a training education college to prepare them for writing scientific papers, that can benefit the development of professionalism. The training of reconstruction of brainstorming problem solving materials module for improving high orther thinking's chemistry college on minerals in the preparation of the final project and the ability to design plagiarism-free papers. Based on the results of the training, the college have been able to browse, and analyze the content of the chemical materials of minerals as a reference material for module development. In addition, the material in the analysis has been clarified based on the education reconstruction model, subject matter until a basicized text has been found. Basic elementary text composite with brainstorming problem solving indicator, becomes the novelty of chemical module of minerals in the context of clay, limestone, and zeolite. The teaching material module produced is the result of the training given and the results of previous research. Keywords: Training, reconstruction module, problem solving thinking